Laparoscopic Repair of Inguinal Hernia : Early Experience in A Tertiary Care Hospital - Roy, Sharmistha; Mondal, Samiron Kumar; Maitra, Tapas Kumar (Bangladesh Critical Care Journal, 2016)
Background : The introduction of laparoscopic techniques has added a new dimension to groin hernia surgery. The laparoscopic repair of inguinal hernia has had a staggering beginning in the surgical arena. Laparoscopic repairs have had to compete with the current gold standard for inguinal hernia repair ie Liechtenstein repair. This study shows the results of laparoscopic inguinal hernia repair in comparison to open repair in a similar group of patients. Methods and materials : This is a prospective study done on 50 male patient of inguinal hernia aging from 18- 65years. Among 50 patients selected for study 25 patient underwent open hernioplasty and 25 patient underwent laparoscopic hernioplasty. In the laparoscopic group, in 20 patients (80%) TAPP procedure was done & in 5 patients (20%) TEP procedure was done. Aims and Objective : The aim of this study is to compare the effectiveness and safety of laparoscopic and conventional open repair, in the treatment of inguinal hernia. Results : Average operating time in open procedure was 55±12 minutes, and in laparoscopic procedure 65±10 minutes. Opoid analgesics were required in 36% patient in open group and 16% in laparoscopy group. Within 7 days most of the patient (76%) in laparoscopic group returned to their normal activity, but in the open group 92% patient required more than 7 days to return to normal activity. Post operative complication like hematoma formation (8%), Testicular pain (8%), retention of urine (3%), and mesh infection (4%) was more in open repair than in laparoscopic repair. In Laparoscopic group 1patient (5%) had bladder injury, and 1 patient (5%) developed illeus. Conclusion : Early results of laparoscopic inguinal hernia repair are encouraging, but the chance of organ injury like bladder, or major vessel injury are more. So laparoscopic repair of inguinal hernia should only be practiced with adequate training and experience in laparoscopic surgery. Bangladesh Crit Care J March 2016; 4 (1): 19-22